(untitled) (Research, Society and Development, 2022)
To analyze women’s experiences of obstetric violence during labor evidenced in the literature. This is an integrative review carried out in November 2021. The search was carried out in the LILACS, PubMed/MEDLINE and BDENF databases. Articles in Portuguese, English and Spanish were included during the period from 2011 to 2021. Findings were discussed based on literature publications. Of the six articles selected in the study, it was observed that obstetric violence was expressed through situations such as verbal aggression, humiliation, lack of privacy and attention, abandonment, unnecessary procedures, poor infrastructure and prohibition of the companion during labor. As well, obstetric violence against black women was also pointed out in the studies. It is necessary to strengthen the discussion and expand the knowledge of professionals and society in general about obstetric violence. Good obstetric practices should also be incorporated into the training of professionals in the academy.